Analysis of the Effect of Population Growth, Dependency Ratio and Per Capita Income Level on Poverty in Central Lombok Regency - Linda Kurnia Ilmiyarni; Akung Daeng; Tuti Handayani (Tinta Emas Institute, 2023)
This study aims to determine the effect between population growth, dependency ratio and per capita income level on poverty in Central Lombok Regency. This type of research is descriptive with a quantitative approach. The data used in this study are population growth data, dependency burden ratio, total per capita income and poverty data from 2010-2022 in Central Lombok Regency. The data collection technique used is documentation, namely by recording and collecting data that has been published by certain agencies or institutions that are relevant to this research. The analytical tool used is Multiple Linear Regression Analysis using the SPSS 17 for Windows program. The results of data analysis show that; (1) The population growth variable has a positive and significant effect on poverty in Central Lombok Regency, (2) The dependency ratio variable is proven to have a positive and significant effect on poverty in Central Lombok Regency, (3) The GDP per capita income level variable (Gross Regional Product) is also proven to have a positive but insignificant effect on poverty in Central Lombok Regency, (4) The population growth variable, dependency ratio and GDP per capita income level are proven to have a positive and significant effect simultaneously on poverty in Central Lombok Regency.